Heptamagnesium bis(phosphate) tetrakis(hydrogen phosphate) with strong hydrogen bonds: Mg(7)(PO(4))(2)(HPO(4))(4) - Assani, Abderrazzak (International Union of Crystallography, 2011)

(untitled)
The title compound, Mg(7)(PO(4))(2)(HPO(4))(4), was synthesized by the hydrothermal method. The structure is based on a framework of edge- and corner-sharing MgO(6) and MgO(4)(OH)(2) octahedra, an MgO(5) polyhedron, PO(4) and PO(3)(OH) tetrahedra. All atoms are in general positions except for one Mg atom, which is located on a crystallographic inversion centre. The OH groups, bridging Mg–(OH)–P, are involved in strong hydrogen bonds. Compounds with the general formula M (7)(PO(4))(2)(HPO(4))(4) (M = Mg, Mn, Fe and Co) are all isostructural with their homologue arsenate Mg(7)(AsO(4))(2)(HAsO(4))(4).